An ethylene response factor (MxERF4) functions as a repressor of Fe acquisition in Malus xiaojinensis - Wei Liu (Nature Portfolio, 2018)
Abstract Iron (Fe) is an essential element for plants; however, its availability is limited as it forms insoluble complexes in the soil. Consequently, plants have developed mechanisms to adapt to low Fe conditions. We demonstrate that ethylene is involved in Fe deficiency-induced physiological responses in Malus xiaojinensis, and describe the identification of MxERF4 as a protein-protein interaction partner with the MxFIT transcription factor, which is involved in the iron deficiency response. Furthermore, we demonstrate that MxERF4 acts as an MxFIT interaction partner to suppresses the expression of the Fe transporter MxIRT1, by binding directly to its promoter, requiring the EAR motif of the MxERF4 protein. Suppression of MxERF4 expression in M. xiaojinensis, using virus induced gene silencing resulted in an increase in MxIRT1 expression. Taken together, the results suggest a repression mechanism, where ethylene initiates the Fe deficiency response, and the response is then dampened, which may require a transient inhibition of Fe acquisition via the action of MxERF4.